DESIGN AND MULTIMEDIA LEARNING PRINCIPLES ON MOOC INDONESIAX - Andreas Rio Adriyanto; Imam Santosa; Achmad Syarief; Irfansyah Irfansyah (Jurnal Cakrawala Pendidikan, 2021)
The “Kampus Merdeka” or “Freedom Campus” policy from the Indonesian Ministry of Education gives students the freedom to participate in learning activities outside their study program. Learning resources can be obtained from online-based learning. One online learning resource is MOOC (Massive Online Open Course), which has gained massive participation. Good quality learning materials can help students construct their knowledge. Indonesian MOOC providers have developed their learning materials, but they are still not optimal in quality. This study aims to analyze the implementation of design and multimedia principles on Indonesian MOOC’s learning materials. The research used a quantitative strategy with the data collection method of visual observation of the IndonesiaX materials compared to those of edX, Udemy, and Coursera materials. Data analysis was based on the visual analysis of 9 design principles and 12 multimedia learning principles. In this research, the findings reveal that the design consistency and icon representation principles are yet to have an optimal grade. The same conditions are also found in implementing the multimedia principles of coherence, redundancy, and modality. The findings in this study are expected to be a consideration for MOOC providers in designing better online learning materials.